Prevalence and Severity of Temporomandibular Joint Disorders in New Students of the Abu Ubaidah bin Al-Jarrah Mahad Foundation - Hanafiah, Olivia Afriyanti; Rusdy, Hendry; Riza, Ahyar; Ayuni HG, Afifah; Felicia (Talenta Publisher Universitas Sumatera Utara, 2023)
Temporomandibular disorders (TMD) can be defined as a clinical problem which comprises of various signs and symptoms, such as pain in the temporomandibular joint or the masticatory muscles, limits in the range of motion, deflection, and clicking/crepitation. The etiology and pathophysiology of TMD has been viewed as multifactorial and complex, few factors were trauma, stress, parafunctional habits, psychological factors, hereditary and occlusal. This community service aimed to assess the prevalence and severity of TMD in freshmen students of Mahad Abu Ubaidah bin Al-Jarrah in 2022 using the Fonseca Anamnestic Index. Community service participants were 157 new students, of which 52.9% were female, and 47,1% were male. Based on the severity, 26,7% were symptom free, 46,5% had mild symptoms, 19,8% had moderate symptoms, and the remaining 7% had severe symptoms. Based on gender, most of the male participants were TMD free, while most female participants had mild TMD symptoms. In conclusion, in this community service showed high prevalence of TMD where only 26,7% of the total participants were TMD free, and the rest had TMD symptoms. Based on gender, TMD symptoms were found more in female participants. Fonseca Anamnestic Index is a useful tool in early detection of the signs and symptoms of TMD.